Measuring Urban Tourist Spillover Effect Toward Rural Area - Tan, Ying Ying; Fam, Soo Fen; Kamarudin, Mohd Fauzi; Wahjono, Sentot Imam; Ong, Boon Zian (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Melaka tourism has attracted huge number of domestic and international tourist every year and becoming a great source of income for the state. However, tourism in Melaka is mostly centralized on the city area of Melaka Tengah causing socioeconomic deprivation and inequality of people in sub urban and rural areas. Consequently, rural tourism work as a solution of development of economic and part of the rural community's diversification policies. Hence, this research is aim to determine the tourist spillover effect from urban exert to rural area. Global and Local Moran, I am used to analysis the data to show the phenomena of spillover of tourist’s flow by correlation. The secondary data is obtained from Tourism Melaka and Department of Statistic Malaysia for further data analysis. The result has shown that tourist spillover happened from Melaka tourist attractions to rural area. Therefore, the tourism in Masjid Tanah a mukim in Alor Gajah district can be expand and innovate to be one of the attraction in Melaka. This suggestion of development will grow the socioeconomic at the rural area by establish more employment apart from agriculture sector, diversify the income of the local citizens as well as encourage them to take part in entrepreneurship.